Is Routine Gastroscopy/Colonoscopy Reasonable in Patients With Suspected Ovarian Cancer: A Retrospective Study - Liu, Guochen; Yan, Junping; Long, Shanshan; Liu, Zhimin; Gu, Haifeng; Tu, Hua; Li, Jundong (Frontiers in Oncology, 2021)
Objective: To evaluate the value of routine preoperative gastroscopy/colonoscopy in patients with suspected ovarian cancer for differential diagnosis and judgment of bowel resection. Methods: All women diagnosed with suspected ovarian cancer who underwent gastroscopy/colonoscopy before surgery in our center were retrospectively identified. Gastroscopy/colonoscopy results and clinical pathology, imaging, and surgical findings were analyzed. Results: 389 patients were included. Among them, 40 (13 gastric and 9 colonic malignancy) were ovarian metastasis. Compared with imaging, gastrointestinal endoscopy showed no statistical advantage in the specificity and sensitivity (99.4% vs. 99.7%, P=1.0; 55.0% vs. 45.2%, P=0.057; respectively). All patients with gastric/colonic cancer metastasize except for one had indicative imaging or tumor marker abnormalities. Three patients with colonic cancer metastases underwent optimal surgery and alive with no recurrence, the other 19 patients experienced palliative chemotherapy. There is no significant difference in the sensitivity of colonoscopy and imaging in predicting intestinal incision (61.5% vs. 43.8%, P=0.804), whereas, the latter had higher specificity (87.8% vs. 74.3%, P=0.001). Conclusions: For patients with suspected ovarian cancer, the incidence of gastrointestinal metastases is low, routine gastroscopy/colonoscopy before treatment is less efficient. Gastroscopy/colonoscopy has limited power to predict the need for gastrointestinal resection before ovarian cancer surgery.